Damage evaluation and performance-based design of double-pier RC bridge subjected to vehicle collision. (December 2021) - Li, R.W.; Wu, H.; Fang, Q.; Wang, D.F.
Abstract: Vehicle collision on reinforced concrete bridge pier (RCBP) frequently occurred all over the world in the past two decades, posing a potential threat to safety of the bridge. However, the impact-resistant design of RCBP in current regulations is only based on the equivalent static force of vehicle impact without considering the damage-performance correlation of the impacted RCBP. This study aims to establish the performance-based design procedure for the typical double-pier RC bridge against vehicle collision. By adopting the refined finite element models of light, medium and heavy trucks with the weight ranging from 3 to 50 t and impact velocity varying from 40 to 120 km/h, 54 numerical simulations of collision scenarios are carried out based on the validated numerical algorithm and material constitutive models. It derives that: (i) the dominated factor that evaluates whether RCBP fails or not under vehicle collision is the peak dynamic shear demand at the base of the RCBP, and related explicit expressions of the peak dynamic shear demand and capacity are further developed and verified; (ii) a new damage index, i.e., the ratio of peak dynamic shear demand to the dynamic shear capacity, is defined to evaluate different damage levels of the RCBP under vehicle collision; (iii) damage-performance correlation of the impacted RCBP is also established, e.g., the bridge is prone to collapse under vehicle collision once damage index exceeds 1.2. Finally, by proposing the impact-resistant performance objectives, the detailed performance-based design procedure is developed according to the importance level of roadway.